(untitled) (Iraqi Journal of Science, 2022)
In this Paper, There are attempts to compare the actual Observation Days in Decametric range (18-28 MHz), For Jupiter received by UFRO Earths’ station with the Prediction Observation Days that the Jupiter can be observed at Jupiter’s suitable location. The Jupiter’s Radio Observations actual data during year 2004, was taken from (Radio JOVE Data Archive website). The determination of the prediction days carried out by using the (Radio-Jupiter pro Jove Edition) software for Jupiter radio storms at UFRO station coordinates. Some Cases are considered according to Jupiter’s altitudes and Sun location at UFRO station Sky. The conclusion is, it could be found that there are (82) number of Predictions Observation Days, and It’s found that the actual number of Observation Days; is only (16) Observation Days.